PENGARUH CAPITAL STRUCTURE, INSTITUTIONAL OWNERSHIP, DAN MANAGERIAL OWNERSHIP TERHADAP PROFITABILITAS PERUSAHAAN - Sapto Bayu Aji; Djasmanuddin Djasmanuddin; Andriono Andriono (Jurnal Solusi, 2021)
Profitability is the end result of a number of company management policies and decisions (Brigham et al., 2001). This study aims to examine the effect of capital structure, institutional ownership, and managerial ownership on company profitability. Capital structure proxied by Debt to Equity Ratio (DER). The company's profitability is proxied by Return on Equity (ROE). The data used are the financial statements of manufacturing companies on the IDX from 2014 – 2018, the results of this study found that capital structure, institutional ownership, and managerial ownership have a positive effect on profitability.